Enough already : learning to love the way I am today - Bertinelli, Valerie, 1960- (Mariner Books, 2022)
"Valerie Bertinelli shares an inspiring blueprint that offers women in midlife support and hope. She shares personal stories that many women will relate to from her past decade: hitting her fifties, taking care of her dying mother, the evolving relationship with her husband, a career change, her relationship with food, and the battle to believe in herself as she is"--